A Bibliometric Exploration of Corporate Sustainable Marketing: Innovation Strategy and Consumer Engagement - Loso Judijanto; Rosyid Nurrohman; Erwin Erwin (West Science Social and Humanities Studies, 2024)
This study provides a comprehensive bibliometric analysis of corporate sustainable marketing, with a focus on innovation strategies and consumer engagement. By analyzing research publications from 1985 to 2024, the study identifies key trends, influential authors, and emerging themes within the field. The results highlight the central role of consumer engagement in sustainable marketing, emphasizing its connection to corporate social responsibility (CSR), customer participation, and green marketing strategies. Innovation is identified as a critical driver in attracting and retaining eco-conscious consumers, with green marketing and business model innovations emerging as essential components of corporate sustainability strategies. Despite the growing body of literature, the study reveals gaps in the integration of advanced technologies such as artificial intelligence (AI) and sustainable business model innovations, suggesting areas for future research. This analysis provides valuable insights for academics, practitioners, and policymakers seeking to understand the evolving dynamics of corporate sustainable marketing and consumer engagement.